Strength of reinforced concrete footings without transverse reinforcement according to limit analysis. (1st April 2016) - Simões, João T.; Faria, Duarte M.V.; Fernández Ruiz, Miguel; Muttoni, Aurelio
Highlights: Strength of RC footings investigated based on kinematical theorem of limit analysis. Relevant interaction between flexural and punching shear regimes. Top reinforcement might play an important role in the punching shear regime. Simplified expressions proposed enabling the calculation of RC footings strength. Good agreement found from the comparison of theoretical and experimental results. Abstract: Isolated footings are reinforced concrete elements whose flexural and punching shear strengths are usually governing for their design. In this work, both failure modes and their interaction are investigated by means of the kinematical theorem of limit analysis. Previous works in this domain have traditionally considered failure mechanisms based on a vertical penetration of a punching cone. In this work, two enhanced failure mechanisms are investigated considering not only a vertical penetration of the punching cone, but also a rotation of the outer part of the footing, allowing to consider the role of both bottom and top reinforcements on the failure load. A rigid-plastic behavior with a Mohr–Coulomb yield criterion is considered for the concrete and a uniaxial rigid-plastic behavior is assumed for the reinforcement bars. The analysis shows that a smooth transition between flexural and punching shear failure occurs, corresponding to a flexural-shear regime. With respect to the punching shear failure regime, it is shown that the top reinforcement might play an important role (a fact usually neglected by previous investigations). Simplified formulations, allowing easy calculation of the load carrying capacity of footings, are derived and compared to the solutions according to limit analysis. Both theoretical and approximated solutions are finally compared with experimental results, showing consistent agreement.